Aberrant Awake Spontaneous Brain Activity in Obstructive Sleep Apnea: A Review Focused on Resting-State EEG and Resting-State fMRI - Wu, Yue; Zhao, Wenrui; Chen, Xinyuan; Wan, Xiaoyong; Lei, Xu (Frontiers in Neurology, 2020)
As one of the most common sleep-related respiratory disorders, obstructive sleep apnea (OSA) is characterized by excessive snoring, repetitive apnea, arousal, sleep fragmentation, and intermittent nocturnal hypoxemia. Focused on the resting-state brain imaging techniques, we reviewed the OSA-related resting-state electroencephalogram (rsEEG) and resting-state functional magnetic resonance (rsfMRI) studies. Compared with healthy control group, patients with OSA presented increased frontal and central δ/θ powers during resting-state wakefulness, and their slow wave activity showed a positive correlation with apnea-hypopnea index (AHI). For rsfMRI, the prefrontal cortex and insula may be the vital regions for OSA, and are strongly related to the severity of the disease. Meanwhile, some large-scale brain networks, such as the default mode network (DMN), salience network (SN) and central executive network (CEN), play pivotal roles in the pathology of OSA. We then discussed the contribution of resting-state brain imaging as an evaluation approach for disease interventions. Finally, we briefly introduced the effects of OSA-related physiological and mental diseases and discussed some future research directions from the perspective of resting-state brain imaging.